Matija Burger, ljubljanski župan 1851-1857 - Bele, Martin (Studia Historica Slovenica, 2017)
The article deals with the life and work of lesser-known mayor of Ljubljana, Matija Burger, who governed the present-day Slovenian capital between 1851 and 1857. It is written on the basis of an analysis of archival and newspaper sources and the already existing Slovenian and Austrian literature. By his education and occupation, Burger was a jurist and lawyer, and he spent most of his time in Ljubljana. Approximately during the March Revolution, he began to engage in politics and was subsequently elected mayor. As mayor, he devoted most of his time to tackling serious financial problems of his city. No construction works took place at that time. Burger finally managed to settle for allowances on direct taxes, which filled the city's cash register at least a little. In April 1857, Burger died unexpectedly, and was buried at the Church of St. Christopher in Bežigrad.
Keywords: Burger, Matija; Ljubljana; lokalna uprava; Slovenija; zgodovina; župani